Raw Material Cost Optimization A Systematic Review of Budgeting Practices in The Manufacturing Sector - Khodijah, Siti; Asro; Santoso, Rachmat Agus; Marliani, Nenda; Purwanto, Asto (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Raw material cost optimization is a critical factor that significantly affects operational efficiency and financial success in the manufacturing sector. In an increasingly competitive business environment, the ability to effectively manage raw material costs impacts not only the profitability but also the competitiveness and long-term sustainability of the company. This study aims to conduct a systematic review of various raw material budgeting practices implemented in the manufacturing industry, analyzing the methodologies and approaches used to optimize raw material costs. The research employs a systematic literature review method, gathering data from Google Scholar and reputable academic journals. Studies were selected based on strict inclusion and exclusion criteria, and the gathered data were qualitatively analyzed to identify the key findings from the relevant articles. The findings of this study indicate that the implementation of information technology, cost standardization, and adaptive procurement strategies play a significant role in improving raw material forecasting accuracy and cost efficiency. Furthermore, the research highlights the importance of structured budgeting in reducing cost variances and improving cost control across manufacturing companies, whether in SMEs or large corporations. This review provides practical insights for companies in developing more efficient budgeting strategies and offers recommendations for further research exploring the impact of industry-specific contextual factors on the effectiveness of raw material budgeting methods.